ANALYSIS OF ECONOMIC SOCIAL IMPACT OF INDUSTRIAL ESTATE TOWARD LOCAL COMMUNITIES - yunita ismail (UPT Penerbitan Universitas Jember, 2017)
The development of industrial zones in the region will have an impact for the area, particularly for the people. The impact area of industry not only in economic, but also social aspects. Therefore the aim of this study was to determine the development aspects of the economy in the period 1981 - 2015 in Bekasi District associated with the development of industrial zones and to determine the development of the social aspect in the period 1981 - 2015 in Bekasi District associated with the development of industrial estates. This research used secondary data from Bekasi District data from 1981 - 2015. The data obtained will be analyzed to see the trend of time series data and to see the changes that occur before and after the existence of an industrial area. Bekasi District election as a study by the consideration that in this district there are many industrial areas (there are seven industrial zones). The development of the economic aspects of labor seen working and not working, harvested area and production of rice, the GDP, export-import and the growing amount of companies. Social aspect seen growing amount of housing, population growth, the development of a number of schools. Increasing the number of companies in the industry is a provider of employment that should be able to absorb the labor force in Bekasi District. However, from the number of jobs available is not able to absorb all workers coming from Bekasi District, jobs are filled by manpower from outside the Bekasi District. Import-export developments showed that the export activity showed a decline but import activity remained stable at a low level. Overall economic indicators shown by the GDP showed a significant increase. Social conditions indicated by fluctuations in the number of inhabitants but the construction of houses is increasing and needs education facilities has also increased.